An investigation into manufacturing performance achievements accrued by Indian manufacturing organization through strategic 5S practices. Issue 4 (9th April 2018) - Randhawa, Jugraj Singh; Ahuja, Inderpreet Singh
Abstract : Purpose: The purpose of this paper is to evaluate the quantitative and qualitative benefits accrued by an Indian automotive parts industry through strategic 5S implementation initiatives. Design/methodology/approach: The study involves evaluation of steps involved in systematic implementation of 5S program methodology in an automotive manufacturing organization and investigation of achievements accrued by the industry through the successful implementation of 5S program. Findings: The empirical results of the study have revealed that effective practice of 5S program brings considerable level of improvements in the quality, production, cost optimizations, employee's morale values and work culture in the manufacturing industry. The industry accrued both tangible and non-tangible benefits through the holistic adoption of 5S principals. 5S principals have been envisioned to further support other quality improvement programs like lean manufacturing initiatives of the organizations. Research limitations/implications: The limitation of the study is that this research has been carried out in only manufacturing industry while similar study will be conducted in the service industry also. Originality/value: Global competition in the manufacturing sector has provided necessary impetus for manufacturing organizations for affecting continuous improvements in manufacturing performance for achieving sustainability and profitability in the competitive market. 5S implementation is the fundamental tool for the overall achievements in both quantitative and qualitative performance enhancements in the manufacturing as well as service organizations.